Functional Characterization of Core Regulatory Genes Involved in Sporulation of the Nematophagous Fungus Purpureocillium lavendulum - Mi Chen (American Society for Microbiology, 2020)
ABSTRACT The nematophagous fungus Purpureocillium lavendulum is a natural enemy of plant-parasitic nematodes, which cause severe economic losses in agriculture worldwide. The production of asexual spores (conidia) in P. lavendulum is crucial for its biocontrol activity against nematodes. In this study, we characterized the core regulatory genes involved in conidiation of P. lavendulum at the molecular level. The central regulatory pathway is composed of three genes, P. lavendulum brlA (PlbrlA), PlabaA, and PlwetA, which regulate the early, middle, and late stages of asexual development, respectively. The deletion of PlbrlA completely inhibited conidiation, with only conidiophore stalks produced. PlAbaA determines the differentiation of conidia from phialides. The deletion of PlwetA affected many phenotypes related to conidial maturation, including abscission of conidia from conidium strings, thickening of the cell wall layers, vacuole generation inside the cytoplasm, production of trehalose, tolerance to heat shock, etc. Comparative analyses showed that the upstream regulators of the core regulatory pathway of conidiation, especially the “fluffy” genes, were different from those in Aspergillus. Besides their roles in conidiation, the central regulators also influence the production of secondary metabolites, such as the leucinostatins, in P. lavendulum. Our study revealed a set of essential genes controlling conidiation in P. lavendulum and provided a framework for further molecular genetic studies on fungus-nematode interactions and for the biocontrol of plant-parasitic nematodes. IMPORTANCE Plant-parasitic nematodes cause serious damage to crops throughout the world. Purpureocillium lavendulum is a nematophagous fungus which is a natural enemy of nematodes and a potential biocontrol agent against plant-parasitic nematodes. The conidia play an important role during infection of nematodes. In this study, we identified and characterized genes involved in regulating asexual development of P. lavendulum. We found that these genes not only regulate conidiation but also influence secondary-metabolite production. This work provides a basis for future studies of fungus-nematode interactions and nematode biocontrol.